Science formative assessment : 50 more strategies for linking assessment, instruction, and learning (Vol. 2) - Keeley, Page. (Thousand Oaks, California : Corwin, 2015)
Deepen scientific understanding with formative assessment! Only by really knowing what your students are thinking can you design learning opportunities that deepen content mastery and meet their individual needs. In this highly engaging resource, internationally respected expert Page Keeley shares 50 new techniques to pinpoint student understanding before, during, and after instruction. In addition to promoting best practices in the classroom, the techniques shared here support learning and link instruction to the Next Generation Science Standards. These flexible assessments can be used with.
Vol. 2.
Includes bibliographical references and index.
Keywords: Science -- Teaching and learning -- Evaluation; Interaction analysis in education; Creative ability in science